Mobile application for donation - Tenedero, Angelou Mae Pancho (Nanyang Technological University, 2021)
Donations in-kind are important if the contributions are centralised with the organisations’ mission such as providing groceries to less income households. In addition, these donations should be in usable condition in order to benefit the recipient.